Contra-Acculturation as Cultural Activism: Resisting‎Assimilation in Migrant Identity Formation - Brintha, K. V.; Rajasekaran , Dr. B. (International Journal of Basic and Applied Sciences, 2025)
Contra-acculturation represents a powerful and intentional form of cultural resistance in which marginalized groups reject the dominant cultural ‎norms imposed upon them by socially and politically powerful entities. Rather than passively assimilate, communities engaged in contra-‎acculturation assert their cultural distinctiveness as a mode of activism and identity preservation. This paper repositions contra-acculturation as ‎a strategic response to assimilation pressures, exploring its multidimensional expressions through cultural practices, values, and identifications. ‎By critically engaging with existing acculturation theories and expanding upon Berry’s bidimensional model, this study introduces a ‎framework that foregrounds agency, dissent, and resilience. Drawing from interdisciplinary insights in psychology, sociology, and migration ‎studies, it further highlights how grassroots heritage initiatives and community-based resistance contribute to psychological well-being and ‎socio-cultural continuity. Empirical studies have demonstrated that engagement in heritage language maintenance and cultural activism ‎positively correlates with migrants’ psychological well-being, reducing acculturative stress and promoting identity coherence (Rivas-Drake et ‎al., 2009; Umaña-Taylor et al., 2009). These findings affirm that contra-acculturation supports both mental health and socio-cultural continuity. ‎In doing so, the paper contributes to both theoretical scholarship and practical discourse on migrant identity formation, with implications for ‎cultural policy, integration frameworks, and social equity‎.